Special Economic Zones as Growth and Anti-growth Poles as Exemplified by Polish Regions - Hanna Godlewska-Majkowska; Agnieszka Komor; Magdalena Typa (Entrepreneurial Business and Economics Review)
Objective: The objective of this paper is to present the effects of special economic zones (SEZ) on the polarisation of public economic space in Polish regions.